The effectiveness of 5S in Utusan Melayu (Malaysia) Berhad / Siti Nurfazira Mohamed Noor - Mohamed Noor, Siti Nurfazira (2017)
5S is a process designed to organize the workplace, keep it clean, and maintain effective and standard conditions. 5S is also known as a set of Standards where the employees need to engage with. There are five main steps in 5S which are Seiri, Seiton, Seiso, Seiketsu and Shitsuke. In Utusan Melayu (Malaysia) Berhad, the implementation of 5S has been done but stills there are problem that had arisen. A research was carried out to find out on "The Effectiveness of 5S in Utusan Melayu (Malaysia) Berhad”. There are 50 employees has been selected for this study. The employees came from different position in the organization. Data and information that has been gathered were analyzed using SPSS. The results stated that, all the hypotheses in this study have moderate relationship. Thus, the researcher has accepted the hypothesis.